2018
DOI: 10.7547/15-181
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Diagnosis and Treatment of Spiral Fracture of the Distal Third of the Tibia Combined with Posterior Malleolus Fracture

Abstract: Computed tomography helped identify most posterior malleolus fractures, and radiography alone might miss it. Intramedullary nailing and posterior malleolus screw fixation were straightforward and effective treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
2
5
0
1
Order By: Relevance
“…In the present review, we have confirmed that the highest incidence of PMFs in this combined injury was mainly focused on spiral TSFs, especially distal third spiral TSFs, which may be due to the injury mechanism and special anatomical structure [ 5 , 31 33 ]. Based on a CT scan or MRI, the mean incidence of PMFs in patients with spiral TSFs and distal third spiral TSFs was 70% (56–88.2%) and 70.4% (35.7–92.3%), respectively.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…In the present review, we have confirmed that the highest incidence of PMFs in this combined injury was mainly focused on spiral TSFs, especially distal third spiral TSFs, which may be due to the injury mechanism and special anatomical structure [ 5 , 31 33 ]. Based on a CT scan or MRI, the mean incidence of PMFs in patients with spiral TSFs and distal third spiral TSFs was 70% (56–88.2%) and 70.4% (35.7–92.3%), respectively.…”
Section: Discussionsupporting
confidence: 53%
“…Seventeen studies reported surgical intervention strategies for PMFs. Among them, 6 studies indicated that surgical fixation should be performed when PMF is recognized [ 1 , 2 , 4 , 5 , 11 , 13 ]; 6 studies suggested that surgical fixation should be performed when PMF is displaced, involving over 25% of the articular surface, instability, or a large fragment [ 6 , 14 , 19 21 , 25 ]; and the remaining 5 studies only reported the percentage of surgical fixation. In patients with the combined injury who met the inclusion criteria, the treatment strategies for PMFs were inconsistent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the same study showed that the size of the posterior tibial edge fragment is mostly underestimated in plain X-rays [1]. Two other recently published studies by Chen et al and Mitchell et al showed similar results for spiral fractures in the distal third of the tibia [6,13]. Spiral tibial shaft fractures, particularly in the middle third of the tibia, were not investigated in these studies.…”
Section: Discussionmentioning
confidence: 83%